Usefulness of NKX2.2 Immunohistochemistry for Distinguishing Ewing Sarcoma from Other Sinonasal Small Round Blue Cell Tumors - McCuiston, Austin (Head Neck Pathol, 2017)
NKX2.2 is a new immunohistochemical marker that has been reported to be sensitive and specific for Ewing sarcoma (ES). It has not, however, been investigated specifically in the sinonasal small round blue cell tumor (SRBCT) differential diagnosis which includes many tumors specific to that site. It has also not been investigated in the newly recognized “adamantinoma-like” variant of ES. Immunohistochemistry for NKX2.2 was performed on 170 poorly differentiated sinonasal neoplasms: 73 squamous cell carcinomas (67 poorly differentiated, non-keratinizing, or basaloid types and 6 nasopharyngeal carcinomas), 46 olfactory neuroblastomas, 8 sinonasal undifferentiated carcinomas (SNUCs), 6 melanomas, 7 Ewing sarcomas, 6 SMARCB1-deficient carcinomas, 6 teratocarcinosarcomas, 5 alveolar rhabdomyosarcomas, 4 solid adenoid cystic carcinomas, 4 NK/T cell lymphomas, 3 NUT carcinomas, and 2 small cell carcinomas. NKX2.2 was positive in 7 of 7 (100%) Ewing sarcomas, including 3 adamantinoma-like variant (all diffuse, 5 strong and 2 weak). It was also positive in 5 of 6 (83%) teratocarcinosarcomas (strong, but focal), 12 of 46 (26%) olfactory neuroblastomas (diffuse, 2 strong and 10 weak), 4 of 6 melanomas (2 diffuse, 2 focal, all weak), and 1 of 2 small cell carcinomas (diffuse and strong). All squamous cell carcinomas, NUT carcinomas, SMARCB1-deficient carcinomas, SNUCs, solid adenoid cystic carcinomas, NK/T cell lymphomas, and alveolar rhabdomyosarcomas were negative. In the sinonasal SRBCT differential diagnosis, NKX2.2 is a useful and very sensitive marker for Ewing sarcoma, including the treacherous adamantinoma-like variant. At the same time, it is not entirely specific, as it will be positive in a subset of other neuroendocrine/neuroectodermal tumors. As a result, NKX2.2 must be utilized as part of an immunohistochemical panel with other markers, especially cytokeratins, melanoma markers, and CD99.